Fatigue strength estimation of single self-piercing riveted joints of steel and aluminium plates under different loading modes. (12th September 2022) - Lee, Young-In; Kim, Ho-Kyung
Self-piercing riveting (SPR) has recently been adopted to join automotive body components because this method can reduce manufacturing costs via product automation while also providing a simpler process. In this study, fatigue tests were conducted using cross-tension and coach-peel specimens with aluminium alloy (A5052) and cold-rolled steel (SPCC) plates to evaluate the fatigue strength of SPR joints. For the combination of a top steel plate and a bottom aluminium alloy plate, designated here as T.S-B.A, the applied load amplitudes corresponding to the fatigue limit in the cross-tension and the coach-peel specimens are approximately 13% and 15% of the monotonic strength, respectively. The fatigue strength of SPR joints of aluminium and steel plates under various types loading conditions can be adequately predicted by the equivalent stress intensity factor amplitude.